Sonographic nystagmus: a case report of lateral semicircular canal benign paroxysmal positional vertigo - Munekata, Yuki; Matsumoto, Chisato; Sakoda, Kento; Takahashi, Yuki (The Ultrasound Journal, 2025)
Background: Nystagmus, a critical diagnostic sign of vertigo and dizziness, reflects disturbances in the vestibular system. The accurate characterisation of nystagmus aids in distinguishing between peripheral and central causes, such as benign paroxysmal positional vertigo (BPPV) and stroke, respectively. Traditional methods for assessing nystagmus involve visual inspection or the use of Frenzel goggles. However, in cases where patients are unable to keep their eyes open owing to severe vertigo, such an evaluation becomes challenging. To date, sonographic imaging has not been used as a diagnostic method for nystagmus. We present a case in which ocular ultrasonography was used to assess nystagmus and aid in the diagnosis of BPPV.Case presentation: A 56-year-old woman presented with recurrent vertigo exacerbated by positional changes. Clinical examination revealed no spontaneous nystagmus or neurological deficits. Because the patient was unable to keep her eyes open during positional testing, ocular ultrasonography was performed using a 9-MHz linear transducer. Imaging revealed direction-changing horizontal nystagmus, consistent with the apogeotropic variant of lateral semicircular canal BPPV. The diagnosis was subsequently confirmed by an otolaryngologist using Frenzel goggles. The patient was conservatively managed.Conclusions: This is the first report on the use of ocular ultrasonography to assess nystagmus. Despite certain limitations, this technique may be a valuable supplementary tool, particularly in settings in which conventional examinations are hindered or unavailable. Ophthalmic sonography has the potential to enhance vestibular assessments in emergency and outpatient settings.